BUREAUCRACY ETHICS IN IMPROVING THE QUALITY OF PUBLIC SERVICES IN THE OFFICE OF TILANGO DISTRICT, GORONTALO REGENCY - Frista Iin Wahyuni (Journal of Economic, Business, and Administration (JEBA), 2022)
The research was conducted to ascertain and analyze (1) the Ethics of Bureaucracy in Oublic Services in Tilango Sub-district Office (2) the inhibiting factors of the ethics of Bureaucracy in Public Service in Tilango Sub-district Office. The research used a qualitative research method. Data collected by using interview, documentation and observation method. Fifteen informants consisted of Tilango Sub-district Chief, Sub-district Secretary, Head of Goverment Section, Head of Social Welfare Section, Head of PMD Section, civil servants, and service recipient communities in Tilango Sub-district Office were determined purposively to be the source of data and information needed. The results of the research indicated that in general the Ethics of Bureaucratic in Tilango Sub-district Office was quite good. This can be seen based on aspects that were indicators of the Ethical Assesment of the Bureaucracy of the state civil apparatus in aspects of discipline, empathy, loyalty, responsibility and obedience and honesty. The results of the interviews indicated that these inditaors were consisdered quite good, only constrained by minor violations commited by state civil apparatus in the form of violations of working hours detremined by the Government. In addition, violations in the form of absences were also carried out by small portion of the state civil apparatus caused by personal problems. The aspect of loyalty and obedience was a very important indicator in the world of work with the level of violations commited, the aspect of loyalty was an absolute thing to be believed and carried out by state civil apparatus loyalty to their work. These things caused the level of loyalty and obedience from state civil apparatus to be very good. Aspects of responsibility and honesty, according to the results of the study found a positive response to the responsibility of state civil apparatus for their work. It can be used as an indicator to show that the Ethics of Bureaucratic in Tilango Sub-district Office was very good, with the high level of honesty of state civil apparatus showed that they had a great sense of responsibility towards their assigned tasks.